Outcome of Cytoreductive Surgery with HIPEC in Ovarian Versus Gastrointestinal Peritoneal Carcinomatosis: A 7-Year Single Centre Experience - Ramadan, Mohamed E; Abdelrahman, Emad M; Zaher, Youssef Abdel; Abostate, Ahmed M (Journal of Coloproctology, 2025)
The use of Cytoreductive Surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) to treat peritoneal carcinomatosis (PC) has grown in popularity in recent years. The aim of the study was to report our own experience concerning morbidities, complications, and survival outcomes in CRS and HIPEC in tumors of gastrointestinal vs ovarian origin.The current study included 62 patients who were admitted by peritoneal Carcinomatosis and eligible for CRS and HIPEC. Follow-up was planned for 5 years.The age of eligible patients was 40.6 ± 3.9 and 39.2 ± 4.6 years in patients with gastrointestinal PC and those with OC respectively. The reported mean Peritoneal Carcinomatosis Index (PCI) was less in Group B (p = 0.056). There was no reported significant difference between both groups regarding intra-hospital mortality, postoperative complication rate, rate of reintervention, or even the length of hospital stays. However, the ICU stay was significantly less in Patients with Ovarian Cancer (OC). The mean Overall Survival (OS) was 31.2 ± 6.2 and 39.1 ± 4.22 in groups A and B respectively with significantly more OS and Disease-free Survival (DFS) reported in Group B (P = 0.046*). The reported 5-year Survival was insignificantly different between both Groups.In certain patient groups with PC from gastrointestinal and Ovarian malignancies, CRS + HIPEC could produce long-term OS with tolerable morbidity and mortality with better outcome OS and DFS in patients with OC.
Keywords: Peritoneal Carcinomatosis; Peritoneal Carcinomatosis Index; Cytoreductive surgery; Hyperthermic Intraperitoneal Chemotherapy. Overall Survival; Disease Free Survival